The influence of target film material and coating on neutron yield and sputtering yield - Jiaxi Liu; Jingbin Lu; Xu Xu; Chengqian Li; Yu Wang; Haotengjiao He (Materials Research Express, 2022)
The long-life, high yield deuterium-deuterium (D-D) neutron tube has become one of the research hotspots. Here, deuterated polyethylene target, heavy water target and titanium target were investigated by Stopping and Range of Ions in Matter (SRIM). The calculation showed that the deuterated polyethylene target, which was a potential target material, had the highest yield at an incident energy of 120 keV. Further, considering the unfavorable factors such as impurity ions and high temperature, the coating was used to protect the target material. Diamond, boron carbide, boron nitride, silicon carbide, and aluminum carbide were selected. The simulation results showed that the diamond composite deuterated polyethylene film had the best sputtering resistance, and the aluminum nitride composite heavy water target film had the lowest sputtering yield. The two coating materials shield the target, reduced the energy loss of incident ions, and provided a new method for the research of high yield and long life neutron tube.